Pengembangan SDM BUMDES Sebagai Penggerak Ekonomi Desa Bunton di Kecamatan Adipala Kabupaten Cilacap - Elok Ainur Latif; Mutia Pamikatsih; Rahmat AlHakim (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
To develop villages, the government gives direct authority to villages to manage their areas independently, one of which is through economic institutions in the village, namely Village-Owned Enterprises (BUMDes). Bunton Village is one of the Adipala District villages with BUMDES in the growing status category. The main obstacle found in BUMDES in Bunton Village is that every work activity needs to be properly administered. Apart from that, BUMDes Bunton has yet to be able to optimize the marketing of its tourism business units. The activities carried out include two things, namely classical assistance and special assistance to BUMDES members in Bunton Village in overcoming the two problems above. The result of this activity is additional knowledge for BUMDes managers regarding Human Resources development.